Do encontro das águas ao Atlântico negro: organização, difusão de frames e os limites do ativismo transnacional no movimento negro brasileiro - Rosa, Alexandre Reis (2011)
My goal in this thesis is to understand the process of transnationalization of Brazilian black movement and its implications for anti-racist struggle in Brazil. In other words, I seek to understand how black Brazilians articulated themselves with the blacks in the world to accomplish their goals. Since today the global black culture has been understood through the metaphor of the “Black Atlantic”, which represents an area of transnational exchange that connects all subjects of the black diaspora, I assume this same metaphor as a starting point for my reflection. However, I am interested in reflecting on one aspect of the Black Atlantic, which is its organizational dimension. If through the Black Atlantic is circulating today a set of contents that are shared by the black community worldwide, such as ideas and practices that are related to religion, music, literature and forms of organization, then we can say that the organization of Brazilian black movement also feeds itself from these multiple dimensions. To develop this argument, the thesis uses the case of the Brazilian black movement to analyze the diffusion process of a racialist transnational frame that is appropriate by the black movement as a basis for making a diagnosis, prognosis and resonance of actions to combat racism in Brazil, and for the establishment of structures for mobilization and action strategies of the movement. However, this appropriation does not occur without problems, because this frame faces other local frames, on a non-racialist character, which causes severe restrictions to transnational activism, once the black movement itself faces a dilemma between maintaining alignment with the transnational frame and seize political opportunities offered by racialism; or relativize this frame making some concessions in their proposals and their organization, in order to adapt to local frames, trading opportunities from these existing restrictions. To understand this dynamic, I propose the metaphor of the “Encounter of Waters” from the Amazon, as a point of argument complementary to the Black Atlantic, since it takes into account the local aspects of anti-racist struggle relying on miscegenation as autonomous identity that does not easily dilutes in the black identity. Besides developing these points, the thesis contributes to better understand the dialectic between global and local, as well as the tensions arising from frames in dispute.